Myanmar : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews economic developments in Myanmar during the 1990s. The economic performance of Myanmar in the 1990s has fallen short of other countries in the region. The Asian crisis has had an unexpectedly limited impact on Myanmar. Following the floating of the Thai baht in June 1997, the free market exchange rate depreciated rapidly, leading to a surge in inflation. Other effects of the crisis have included a slowing in growth of tourist arrivals and delayed receipt of gas export revenues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet